Induced ovulation and timed recovery of suitably sized embryos for transfer in mares - Lopes, Giulia V [UNESP]; Camargo, Giovana S [UNESP]; Sambi, Giovanna N [UNESP]; Assoni, Karina R [UNESP]; Denadai, Renan [UNESP]; Bergfelt, Don R; Canesin, Heloisa S [UNESP]; Monteiro, Gabriel A; Ignácio, Fernanda S [UNESP] (Elsevier, 2023)
Studying the size of equine embryos recovered from uterine flushes 8-9d after ovulation has established that size and age of embryos post-ovulation are directly related (Cuervo-Arango et al., Theriogenology. 2018; 115: 90-93). In the field, daily tracking and detection of ovulation are not practical in a commercial embryo transfer program. Considering that induced ovulation with deslorelin acetate (DES) occurs in most mares 38-44h after administration (Spencer et al., Theriogenology. 2022: 140-148), estimated time of ovulation induction may be used to predict the time of embryo recovery. The objective herein is to evaluate embryo size at the time of recovery after DES administration and ovulation and determine its fit within a 0.25mL or 0.5mL embryo transfer straw. Healthy, adult cycling mares (n=15 total) were subjected to ovulation induction with 1mg of DES i.m. when the dominant follicle first reached 35mm. Mares were artificially inseminated 24h later and monitored daily to detect ovulation (D0) with uterine flushes done 8 (D8) or 9 (D9) d later. Recovered embryos were measured by a micrometric ruler and compared: 1) D8 vs D9 after ovulation, 2) <250h vs >250h after DES, and 3) fit into 0.25mL (embryos <1500µm) vs 0.5mL (embryos from 1500 to 2500 µm)straws. Student's t-tests were used to analyze the size of embryos on D8 (n=8) vs D9 (n=5) after ovulation and <250h (n=8) vs >250h (n=7) after DES. Z-score test was used to analyze the probability of fit into a 0.25mL vs 0.50mL straw. All mares ovulated 24-48h after DES. There was no difference (P=0.25) in size of embryos recovered on D8 (mean diameter = 828±193.4µm) vs D9 (mean diameter = 1320±411µm) after ovulation. Relative to induced ovulation, embryos recovered <250h after DES (mean diameter = 828±193.4µm) were smaller (P=0.0474) than those recovered >250h after DES (mean diameter = 1971±514µm). The probability of embryos fitting into a 0.25mL straw was 89% for D8, 57.8% for D9, 89% for <250h, and 36.5% for >250h. Correspondingly, the probability of embryos fitting into a 0.5mL straw was 99.9% for D8, 90% for D9, 99.9% for <250h, and 65.1% for >250h. Thus, these preliminary results indicate that, without daily tracking and detection of ovulation, the predicated time from induced ovulation to recovery of embryos at 236-247h (i.e. 10 days) to 258-264h (i.e. 11 days) after DES yield suitably sized embryos for transfer using a 0.25 or 0.5mL straw.